2023
DOI: 10.17524/repec.v17i1.3214
|View full text |Cite
|
Sign up to set email alerts
|

Gerenciamento de resultados e legibilidade das notas explicativas: manipulações nas evidenciações contábeis

Abstract: Objetivo: Este estudo objetiva verificar a relação entre o nível de legibilidade das notas explicativas e as práticas de gerenciamento de resultado por empresas listadas na [B]3 entre os anos de 2010 e 2018. Método: Foi utilizado um modelo econométrico apresentando a legibilidade como variável dependente e gerenciamento de resultados como variável independente principal, além de variáveis de controle, sendo analisado por meio de regressão de dados em painel com efeitos fixos controlados por ano e se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Samantha Valentim Telles / Bruno Meirelles Salotti 2018; Borges & Rech, 2019;Silva et al, 2020;Cadorin & Theiss, 2022;Mendes & Lucena, 2022;Souza & Borba, 2022;Sena et al, 2023). The lack of a relationship between readability and information quality, as found by Sena et al (2023), or a firm's disclosure strategy that uses narrative complexity to maintain social legitimacy, as found by Hassan et al (2019), could explain this.…”
Section: Fog Number Of Pagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Samantha Valentim Telles / Bruno Meirelles Salotti 2018; Borges & Rech, 2019;Silva et al, 2020;Cadorin & Theiss, 2022;Mendes & Lucena, 2022;Souza & Borba, 2022;Sena et al, 2023). The lack of a relationship between readability and information quality, as found by Sena et al (2023), or a firm's disclosure strategy that uses narrative complexity to maintain social legitimacy, as found by Hassan et al (2019), could explain this.…”
Section: Fog Number Of Pagesmentioning
confidence: 99%
“…For our study, we used an adapted version of this metric specifically designed for the Portuguese language, as developed by Martins et al (1996) and used in previous studies (e.g. Telles & Salotti, 2020;Sena et al, 2023) To measure understandability, we used the Meaning Identification Test (MIT), which employs paraphrases that retain the meaning of the original sentence, as well as paraphrases that change the meaning. Jones and Smith (2014) examined several measures for assessing understandability in accounting texts and concluded that the MIT comprehension test yielded superior results compared to other measures in terms of measuring passage comprehension.…”
Section: Readability and Understandability Of Notes To Financial Stat...mentioning
confidence: 99%
See 1 more Smart Citation